2018
DOI: 10.1186/s13570-018-0121-9
|View full text |Cite
|
Sign up to set email alerts
|

Enteric methane output from selected herds of beef cattle raised under extensive arid rangelands

Abstract: Extensively raised beef cattle contribute to the highest levels of enteric methane (CH 4 ) gas emissions among all livestock. Expensive techniques and logistics hinder monitoring of such gas. Therefore, the objective of this study was to use an inexpensive laser methane detector (LMD) apparatus to determine the enteric CH 4 levels from a herd of beef cows raised on semi-arid rangelands. A total of 24 cows were selected from Boran and Nguni cows (n = 12 per breed) from two different farms. The parities of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…This is more in line with EDGAR v4.3.2 compared to v5.0 at 30°S-90°S. A study performed in South Africa, concluded that Nguni and Boran cows produce more CH 4 per kilogram live weight of cow during the dry season (mid-May to October) compared to the wet season (November to early May) (Mapfumo et al, 2018), which partly corresponds to EFMM emissions peaking in August-October in EDGARv4.3.2 at 30°S-90°S. In contrast, Arndt et al (2018) measured emissions from Jersey cattle (primary breed) in California and found that animal housing (enteric fermentation as major source) had no seasonality, which corresponds well to EDGAR v5.0.…”
Section: Seasonal Cycle Of Ch 4 Emissionssupporting
confidence: 65%
“…This is more in line with EDGAR v4.3.2 compared to v5.0 at 30°S-90°S. A study performed in South Africa, concluded that Nguni and Boran cows produce more CH 4 per kilogram live weight of cow during the dry season (mid-May to October) compared to the wet season (November to early May) (Mapfumo et al, 2018), which partly corresponds to EFMM emissions peaking in August-October in EDGARv4.3.2 at 30°S-90°S. In contrast, Arndt et al (2018) measured emissions from Jersey cattle (primary breed) in California and found that animal housing (enteric fermentation as major source) had no seasonality, which corresponds well to EDGAR v5.0.…”
Section: Seasonal Cycle Of Ch 4 Emissionssupporting
confidence: 65%
“…The LMD equipment measures the concentration of CH4 between the equipment and the target point. It is based on infrared absorption spectroscopy and measures CH4 values as a plume [24][25][26]. Thus the measurements are in parts per million-metre (ppm-m) [25].…”
Section: Methodsmentioning
confidence: 99%
“…The equipment operates normally in the temperature range between 0 and 40 °C, in the humidity range of 20-90%, with a reaction time of 0.1 seconds. The LMD can detect CH4 concentrations between 1 and 50,000 ppm within a distance of up to 150 m. Gas column density was measured by directing the auxiliary LMD targeting (visible HeNe) laser beam at the nostrils of goats at a distance of 1.5m from the goat [26]. Prior the commencement of the measurements for each day, the LMD was off-set to adjust it to the ambient CH4.…”
Section: Methodsmentioning
confidence: 99%
“…Reported numbers of measurements per animal range from 1 [14] to 72 per cow [32] and 63 per goat [26]. When deciding on the appropriate number of replicates per animal, there is a trade-off between workload and invasiveness on the one hand and the quality of the data on the other.…”
Section: Total Number Of Repeats Per Animalmentioning
confidence: 99%